INFLUENCE OF RELIGION ON PAKISTANI MAINSTREAM MEDIA: AN APPLICATION OF BELIEFS INTO ACTION SCALE FOR JOURNALISTS - DR. RIAZ AHMAD SAEED; DR. AQEEL AHMED; DR. ULFAT NISA (Hamdard Islamicus)
This cross-sectional survey explored the influence of religion on Pakistani journalists by applying the Belief into Action Scale. The study based on responses from 300 journalists, discovered influence of religious beliefs held by the journalists of digital and electronic media on their professional (journalistic) practices. The findings demonstrated that the Belief into Action Scale was a highly reliable measure to assess the influence of religion on Pakistani journalists. The results observed that Pakistani male journalists were more influenced by religious beliefs than their female counterparts. Similarly, the journalists employed in digital media setups displayed a greater inclination towards faith while performing their professional duties than the ones belonging to electronic media organizations. Moreover, the study participants with more experience and increasing age were found to be more practically religious and tended to be more influenced by their religious beliefs while fulfilling their professional responsibilities. However, this research discovered that the journalists holding higher academic qualifications showed a lesser tendency to practicing religion than their contemporaries with lower educational qualifications.